Lithium Ion Repulsion‐Enrichment Synergism Induced by Core–Shell Ionic Complexes to Enable High‐Loading Lithium Metal Batteries. (24th September 2021) - Meng, Junwei; Lei, Meng; Lai, Chuanzhong; Wu, Qingping; Liu, Yangyang; Li, Chilin
Abstract: A core–shell additive with anionic Keggin‐type polyoxometalate (POM) cluster as core and N‐containing cation of ionic liquid (IL) as shell is proposed to stabilize Li‐metal batteries (LMBs). The suspended POM derived complex in ether‐based electrolyte is absorbed around the protuberances of anode and triggers a lithiophobic repulsion mechanism for the homogenization of Li + redistribution. The gradually released POM cores with negative charge then enrich Li + and co‐assemble with Li. The Li + repulsion‐enrichment synergism can compact Li deposition and reinforce solid electrolyte interphase. This sustained‐release additive enables Li∥Li symmetric cells with a long lifetime over 500 h and 300 h at high current densities of 3 and 5 mA cm −2 respectively. The complex additive is also compatible with high‐voltage Li∥LiNi0.8 Co0.15 Al0.05 O2 (NCA) cells. Even with a NCA loading as high as ca. 20 mg cm −2, the additive contained Li∥NCA cell can still cycle for over 100 cycles at 2.6 mA cm −2 . Abstract : A core–shell additive with anionic Keggin‐type polyoxometalate (POM) cluster as core and N‐containing cation of ionic liquid (IL) as shell is proposed to stabilize Li‐metal batteries (LMBs). The gradually released POM cores with negative charge enrich Li + and co‐assemble with Li. The Li + repulsion‐enrichment synergism can compact Li deposition and reinforce the solid electrolyte interphase.